Depression severity and verbal comprehension in children and adolescents with a major depressive episode - Trasolini, Monia; Serra, Giulia; Iannoni, Maria Elena; Andracchio, Elisa; Apicella, Massimo; Maglio, Gino; Menghini, Deny; Vicari, Stefano (Frontiers in Psychiatry, 2024)
Severe depression is a prevalent psychiatric illness in children and adolescents associated with high levels of morbidity, disability, and high risk of suicidal behavior. Cognitive factors associated with depression severity in juveniles have been poorly reported. We investigated the relationship between depression severity and intelligence quotient (IQ) with its subscales in 65 juveniles (aged 10-17 years) with a current major depressive episode, evaluated at the Mood Disorder Program of Bambino Gesù Children's Hospital in Rome. Pearson correlation analyses were followed by Benjamini Hochberg correction, and linear multivariable regression model. Depression severity as measured with the total score of the Children Depression Rating Scale-Revised (CDRS_R) was positively associated with Verbal Comprehension Index (VCI, Pearson's r = 0.309 [0.042 to-0.534]; p = 0.024). CDRS-R subscales positively associated with VCI by Pearson correlation were depressed feelings, suicidal ideation, excessive weeping and reduced facial expressions. Suicidal ideation was the only factor independently and significantly associated with higher VCI in multivariable linear regression model. Suicidal ideation was significantly and independently associated with higher verbal comprehension, indicating that depressed juveniles with better verbal ability might be a greater risk of showing suicidal ideation.